Integral Human Development in Higher Education and HIV-AIDS Advocacy Work of Filipino Artists - Brian Saludes Bantugan (PT FORMOSA CENDEKIA GLOBAL, 2023)
A research funded by the National Research Council of the Philippines, this study looked into the ideas informing artworks and networks of participation and influence (NPI) of the artist-advocates who help address integral human development (IHD) concerns in the context of the HIV-AIDS problem in the Philippines that can help enhance the three foundational areas of university training of Paulinian IHD artist-advocates in St. Paul University Manila. Using a qualitative triangulated descriptive research design, it was conducted in five major cities of the Philippines. Unstructured interviews of purposively sampled key artist-advicates using digital technologies and their digitally enriched artworks were conducted to surface data analyzed via hermeneutic audio-visual document/textual analysis. Findings revealed four ideas and four NPI.